A Ti/Ti-Based-Metallic-Glass Interpenetrating Phase Composite with Remarkable Mutual Reinforcement Effect. (14th May 2014) - Mu, J.; Zhu, Z. W.; Zhang, H. F.; Zhang, H. W.; Fu, H. M.; Li, H.; Wang, A. M.; Hu, Z. Q.
Abstract : A Ti/Ti-based-metallic-glass interpenetrating phase composite (IPC) was prepared by infiltrating the Ti 34.3 Zr 31 .5 Ni 5 .5 Cu 5 Be 23 .7 melt into the porous Ti skeleton. Porous Ti limits the shear band (SB) propagation and promotes the SB multiplication, leading to the improved ductility. Moreover, the interpenetrating phase structure shows a mutual reinforcement effect for both amorphous and crystalline phases, making IPC possess higher strength than that calculated by the models held for the conventional composites. This finding will suggest a new way for preparing composites with high strength and ductility.